Evidence of carcinogenicity in humans of water-soluble nickel salts - Grimsrud, Tom K (BioMed Central, 2010)
BACKGROUND: Increased risks of nasal cancer and lung cancer in nickel refiners have been investigated scientifically and discussed since they were detected in the 1930s. Nickel compounds are considered to be the main cause of the cancer excess. Parts of the nickel producing industry and their consultants oppose the classification of water-soluble nickel salts as human carcinogens, and argue that the risk in exposed workers should be ascribed to other occupational exposures and smoking. DISCUSSION: Respiratory cancer risks in Welsh, Finnish, and Norwegian nickel refiners add to the evidence of carcinogenicity of water-soluble nickel. In Norwegian refiners, the first epidemiological study in 1973 identified high risks of lung cancer and nasal cancer among long-term electrolysis workers. Risk analyses based on exposure estimates developed in the 1980s supported the view that water-soluble nickel compounds were central in the development of cancer. Recently, new exposure estimates were worked out for the same cohort based on personal monitoring of total nickel and chemical determination of four forms of nickel. Additional data have been collected on life-time smoking habits, and on exposure to arsenic, asbestos, sulphuric acid mists, cobalt, and occupational lung carcinogens outside the refinery. After adjustment for these potential confounding exposures in case-control analyses, the risk pattern added to the evidence of an important role of water-soluble nickel compounds as causes of lung cancer. These Norwegian cancer studies rely on national Cancer Registry data, considered close to complete from 1953 onwards; and on National Population Register data continuously updated with mortality and emigration. Canadian mortality studies--perceived to offer the strongest support to the industry position not to recognise carcinogenicity of water-soluble nickel--appear to suffer from limitations in follow-up time, loss to follow-up, absence of risk analysis with individual exposure estimates, no confounder control, and a likely underestimation of cancer mortality. CONCLUSIONS: Rejection to recognise water-soluble nickel as a human carcinogen seems to contradict material epidemiological evidence that demonstrates a strong association between water-soluble nickel compounds and risks of lung cancer and nasal cancer. Independent international scientific bodies have classified nickel compounds as carcinogenic to humans, inclusive of water-soluble nickel.